Students’ Perception of Using HumataAi in Improving Writing Ability - Sabila Kamalia; Emeliya Sukma Dara Damanik (Universitas Cokroaminoto Palopo, 2025)
The purpose of this study was to found students' perceptions of the use of Humata Ai in writing. This study discusses student perceptions on using Humata Ai in improving writing ability. This study used a qualitative method with a phenomenological approach, involving 15 students from the 8th semester majoring in English education department, collecting data using questioners and interviews, the questioner used was 10 questions and Likert Scale (strongly agree, agree, doubt, disagree, strongly disagree). The data were analyzed using thematic analysis. The results showed that there were several main findings in this study: (1) Students feel that the use of HumataAi can improve their ability to write, with a percentage of 53.3% agreeing. (2) HumataAi can make it easier for students to write with a percentage of students agreeing 46.6%. (3) Students' concerns about dependence on HumataAi with a percentage of students agreeing to this as much as 53.3%.(4) Students feel that the writing produced by HumataAi will be detected plagiarism with a percentage of students agreeing 33.3%. an fast. The researcher highly recommends this Ai to be used by students as a tool for finding ideas in writing.